European Smart Tourism Tools Observatory - Galvão, A.; Cosme, D.; Brito e Abreu, F. (2023)
This report delineates the methodology and results employed in building the initial iteration of the European Online Observatory on Smart Tourism Tools (STT). The initial section presents the work conducted to establish an agreed-upon definition of smart tourism tools, a concise overview of studies pertinent to the subject, a description of the methodology employed, and a discussion of the findings. The results of the aforementioned work enabled the generation of a consensual definition of STT and the extraction of the principal variables, with consideration given to their relative weight, that comprise an STT. The aforementioned results permit the construction of a smartness index, which will classify the offerings showcased in the Observatory. This phase is currently being concluded. Subsequently, the methodology employed in the development of the European Smart Tourism Tools Observatory is presented. The methodology encompasses two distinct domains: web mining and smart extraction, transformation, and loading of textual data from STT descriptions, facilitated by large language models and conventional data processing techniques; and the development and deployment of the platform that constitutes the observatory. This inaugural iteration of the Observatory incorporates STT data from a prominent international repository. However, the Smartness index, contingent upon the completion of the STT definition task, has yet to be calculated. The report concludes with an examination of the dissemination and maintenance of the Observatory.